Multi agent mobile robots : motion planning in hazardous environment - 426614 Eid Mokhtar (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2002